Oxygen Activation by N-doped Graphitic Carbon Nanostructures. Issue 1725 (23rd February 2015) - Noffke, Benjamin W.; Li, Qiqi; Li, Liang-shi; Raghavachari, Krishnan
ABSTRACT: Fundamental understanding of the oxygen reduction reaction (ORR) electrocatalyzed by nitrogen-doped carbon requires a well-defined structure to correlate structure to function. Well-characterized N-doped graphitic nanostructures derived from benzene derivatives have been synthesized in our group, and shown to catalyze a four-electron ORR under alkaline conditions. Density functional theory calculations have been performed on a model N-doped graphitic nanostructure, C50 N2 H20, to determine an oxygen activation mechanism. With guidance through an experimentally determined Pourbaix diagram, DFT calculations clearly indicate that the catalyst must undergo a 2e −, 1H + reduction to generate a reactive carbanionic intermediate that activates oxygen with a spin inversion.